Therapeutic chemical screen identifies phosphatase inhibitors to reconstitute PKB phosphorylation and cardiac contractility in ILK-deficient zebrafish - Pott, Alexander; Shahid, Maryam; Köhler, Doreen; Pylatiuk, Christian; Weinmann, Karolina; Just, Steffen; Rottbauer, Wolfgang (Biomolecules, 2018)
Patients with inherited dilated cardiomyopathy (DCM) often suffer from severe heart failure based on impaired cardiac contractility leading to increased morbidity and mortality. Integrin-linked kinase (ILK) as a part of the cardiac mechanical stretch sensor was found to be an essential genetic regulator of cardiac contractility. Integrin-linked kinase localizes to z-disks and costameres in vertebrate hearts and regulates the activity of the signaling molecule protein kinase B (PKB/Akt) by controlling its phosphorylation. Despite identification of several potential drug targets in the ILK signaling pathway, pharmacological treatment strategies to restore contractile function in ILK-dependent cardiomyopathies have not been established yet. In recent years, the zebrafish has emerged as a valuable experimental system to model human cardiomyopathies as well as a powerful tool for the straightforward high-throughput in vivo small compound screening of therapeutically active substances. Using the ILK deficient zebrafish heart failure mutant main squeeze (msq), which shows reduced PKB phosphorylation and thereby impaired cardiac contractile force, we identified here, in an automated small compound screen, the protein phosphatase inhibitors calyculin A and okadaic acid significantly restoring myocardial contractile function by reconstituting PKB phosphorylation in msq ILK-deficient zebrafish embryos.
Gesehen am 26.08.2020